De pessoa com deficiência auditiva a surdo: embates dialógicos e objetificação colonial no processo de transição identitária - Lima, Daniele Caroline Gonçalves (2020)
By an inclusive perspective, the special education and deaf studies have fought battles in the academic field regarding the deaf people along the last years. In what concerns to the social issue, there were many distinct approaches and focuses adopted, which even culminated in different terminologies. One of the most discussed example in scientific literature is the terms “person with hearing disability” in opposition to “deaf person”. Above any controversies around the option for one of those terms, there is the fact that people with hearing disabilities, whether exposed or not to signal languages, started being understood by different perspectives. As a result, there are very few researches about them. With that said, this research aims to identify the dialogical clashes and the forms of colonial objectification in the process of transition of identity of people with hearing disabilities. To do so, our theoretical perspective is based on the studies about colonial objectification (BHABHA, 1994; 1998; FANON, 1681; BOAVENTURA SANTOS E MENEZES, 2009), identity (HALL, 2006; BAUMAN, 2005), the conception of language of Bakhtin Circle (BAKHTIN, 1997; 2002; 2010; 2011; 2017; FARACO, 2009; VOLÓCHINOV, 2017; BRAIT, 2005; 2017; SOBRAL, 2019) and, finally, Deaf Culture, (PERLIN, 1998; 2003; 2016; STROBEL, 2008; 2009; QUADROS, 2019; LADD, 2013). Our subjects were six (6) deaf students of the undergraduate course Letras – Libras and Portuguese Language at UFRN. The data were collected through a half-structured interview, in Libras, using the round of conversation format. From this analysis, the following categories emerged: transition of identity, colonial objectification and dialogical clashes. We observed that the people with hearing disabilities enjoy the possibility of transition of identity when they get in touch with signal language and with other deaf people. In this process, the forces of language are accentuated, once they enable the Identity of the deaf to substitute the reach of the hearing standard. However, those forces remain in the process of boiling, since forces of containment/monologization and resistance/subversion also exist in deaf communities. That said, we evoke the importance that deaf ways of being are kept away from dichotomies oriented towards normality / abnormality, and that we can unlearn to learn, so that speaking deaf people can (re)exist.